2017
DOI: 10.1002/2016ja023271
|View full text |Cite
|
Sign up to set email alerts
|

Identification of scintillation signatures on GPS signals originating from plasma structures detected with EISCAT incoherent scatter radar along the same line of sight

Abstract: Ionospheric scintillation originates from the scattering of electromagnetic waves through spatial gradients in the plasma density distribution, drifting across a given propagation direction. Ionospheric scintillation represents a disruptive manifestation of adverse space weather conditions through degradation of the reliability and continuity of satellite telecommunication and navigation systems and services (e.g., European Geostationary Navigation Overlay Service, EGNOS). The purpose of the experiment present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 48 publications
(85 reference statements)
3
30
0
Order By: Relevance
“…Item 1 agrees with a case study of Forte et al [, Conclusions] in that F region plasma density perturbations have two‐dimensional surface structures. Note also that “ground‐based” GNSS receivers at auroral latitudes may also observe enhanced phase scintillations when the LOS is aligned with the L shell: but the effect is not conspicuous [ Forte and Radicella , ].…”
Section: Discussionsupporting
confidence: 89%
“…Item 1 agrees with a case study of Forte et al [, Conclusions] in that F region plasma density perturbations have two‐dimensional surface structures. Note also that “ground‐based” GNSS receivers at auroral latitudes may also observe enhanced phase scintillations when the LOS is aligned with the L shell: but the effect is not conspicuous [ Forte and Radicella , ].…”
Section: Discussionsupporting
confidence: 89%
“…Many characteristics of scintillation are well-studied [1,7,11,28,8,20,17,44]. It has been shown that scintillation activity varies with operating frequency, local time, season, geomagnetic activity level(planetary K-index, K p ), and the 11-year solar cycle [46,29,38,7,28,20].…”
mentioning
confidence: 99%
“…However, to illustrate the utility of the IPE parameters for quantitative structure analysis, Figure 8 shows a color-coded display of the segment CsdB estimates plotted at the 350-km path intercept point. The results provide better structure definition than the S4 or rms phase measures typically used, for example, in the extensive study by Forte et al (2016).…”
Section: Stochastic Tec Diagnostic Measurementsmentioning
confidence: 94%